2009
DOI: 10.1007/s10236-008-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven wave heights in the German Bight

Abstract: Wind speed, friction velocity and significant wave height data from the FINO1 platform in the southern German Bight 45 km off the coast for the years 2004 to 2006 have been evaluated and related to each other. The data show a clear dependence of the hourly mean wave height to the hourly mean friction velocity and wind speed. Wave heights increase with decreasing stratification and increasing fetch. Synoptic weather patterns for the highest wave heights in the southern German Bight are determined. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…While many values for k are given we chose a middle value of k = 0.15 that corresponds to the open ocean data taken in the North Atlantic. More recent results from a study in the German Bight [ Emeis and Turk , 2009] closely match this equation.…”
Section: Air Entrainment By Gas Bubblessupporting
confidence: 73%
“…While many values for k are given we chose a middle value of k = 0.15 that corresponds to the open ocean data taken in the North Atlantic. More recent results from a study in the German Bight [ Emeis and Turk , 2009] closely match this equation.…”
Section: Air Entrainment By Gas Bubblessupporting
confidence: 73%
“…Furthermore, storm Britta caused extremely high waves in the German Bight, as evidenced by structural damage to the FINO1 wind farm research platform (45 km offshore) at heights up to 20 m above the mean sea level (see e.g. Emeis and Türk 2009, and references therein).…”
Section: Modeling Of a Strong Storm Surgementioning
confidence: 99%
“…In a series of studies of Britta, e.g., Brusch et al (2008), Behrens and Günther (2009), Emeis and Türk (2009), Pleskachevsky et al (2012) and Kettle (2015b), the following features have been observed:…”
Section: Introductionmentioning
confidence: 94%
“…At the same time, measurements have been analyzed extensively for understanding the development of this storm (e.g. Emeis and Türk (2009)). Storm Britta is characterized of strong and highly fluctuating mean wind speed and unusually high waves in the North Sea, where FINO 1 experienced a 20-year return value for the significant wave height and where structural damages on the FINO 1 platform A c c e p t e d M a n u s c r i p t…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation